Effectiveness of Ball Standing Throw Training on Heading Ability in Football Games - Jud; Marsuna; Sariul; La Ode Rusdin; Astia Febriani Asrin (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This study aims to determine the effectiveness of ball standing throw training on heading ability in soccer games. The method used in this study is an experimental research method with a pre-test-post-test design. The population in this study were all students who participated in extracurricular activities at State Senior High School 5 Kendari students totaling 25 people. The sampling technique used the total sampling technique, namely the entire population used as a sample of 25 people. The instrument used to measure soccer heading ability was the heading test. The training method used was ball standing throw training with a modified ball load. The sampling technique used the total sampling technique, namely the entire population used as a sample of 25 people. Based on the data analysis, it can be seen that the t-test value is 15.455 with a significance of 0.000 <0.05, meaning that between the implementation of the pretest and posttest of heading ability in soccer games there was an increase in the implementation of the posttest using ball standing throw training. Based on the average pretest value of 7.02 and the average posttest value of 8.13.